Disconnection syndromes and injury to neural systems after ischemic stroke - Schwarz, Anne; Holl, Christina K.; Brinkman, Lorie; Stehman, Andrea J.; Cardoso Ferreira, Isabel; Soleimani, Nina; Farahmand, Eden; Settle, Maeve; Sakthi, Shivani; Vo, Ivy; Olivares, Natalie; Song, Min-Keun; et al. (Frontiers in Stroke, 2026)
BackgroundStroke-related impairments present in wide-ranging combinations, including cognitive and upper extremity (UE) sensorimotor deficits, complicating an understanding of their relationship with the anatomy of injury. Here, we hypothesized that deficits in UE sensorimotor function, mood, and cognition would be associated with distinct patterns of neural injury, and we explored whether complex outcome measures that make both cognitive and motor demands are more vulnerable to injury-related disconnection after stroke.MethodsSubject testing included elementary sensorimotor behaviors (shoulder and finger strength [SAFE], Fugl-Meyer Assessment [FMUE], and wrist proprioception [WPST]), complex behaviors that require substantial motor and cognitive control (Box and Blocks Test [BBT] and Trail Making Test-A [TMT-A]), cognition (Montreal Cognitive Assessment [MoCA]), and mood (Geriatric Depression Scale). Infarcts were outlined on clinical scans and used to compute lesion volume, injury to the corticospinal tract (CST) as well as thalamocortical sensory tract, and measures of structural network disconnection. Associations between lesions and behavior were examined using three methods: [1] voxel-lesion-symptom mapping (VLSM) to identify lesioned voxels associated with behavioral deficits; [2] correlation, to identify bivariate relationships between neuroimaging and behavioral measures; and [3] LASSO regression to identify the most behaviorally relevant variables among neuroimaging and clinical measures.ResultsStroke patients (n = 55, mean age 69.2, 42% females) had lesion volumes ranging from 0.1 to 354.9 (mean 30.9) ml and averaged 10.4 ± 4.9 days post-stroke. Deficits in all three elementary UE sensorimotor behaviors (SAFE, WPST, FMUE) correlated with extent of injury to CST not disconnection measures, with VLSM largely consistent, while deficits in complex motor and cognitive behaviors (BBT and TMT-A) were related to widespread structural disconnection between brain networks. LASSO models that consider all neuroimaging and clinical measures revealed complex patterns of disconnections across behaviors.ConclusionThese findings indicate that elementary UE sensorimotor behaviors are related to the integrity of regional sensorimotor system structures, but that more complex motor and cognitive behaviors are more related to intact structural connectivity between multiple brain networks.